How to run seminars & workshops presentation skills for consultants, trainers, teachers, and salespeople - Jolles, Robert L. 1957- (Hoboken, New Jersey Wiley, 2017)
"How to Run Seminars and Workshops has taught tens of thousands of people how to sell, teach, stand up, and deliver an effective training session on almost any subject in almost any setting. Updates to the Fourth Edition include: - New Chapter: Taking your training online. As podcasts continue to take the place of live deliveries, and companies like Udemy offer shorter, simpler online delivery option, those who deliver seminars and workshops must adjust their approaches to delivery."--Provided by publisher.
Includes bibliographical references.
Keywords: Seminars -- Handbooks, manuals, etc; Workshops (Adult education) -- Handbooks, manuals, etc; Meetings -- Handbooks, manuals, etc